Nerve Blockage Attenuates Postoperative Inflammation in Hippocampus of Young Rat Model with Surgical Trauma - Yi He; Zhi Li; Yun-Xia Zuo (Mediators of Inflammation)
It is hypothesized that central nervous system inflammation induced by systematic inflammation due to surgical trauma plays a critical role in postoperative cognitive dysfunction. The potential inhibitory effect of nerve blockage with local anesthetics on peripheral inflammatory response has been reported. We hypothesize that nerve blockage may be effective in reducing postoperative inflammation and cognitive decline. The rats at the age of 4 weeks were subjected to general anesthesia and humeral fracture fixation, in combination with brachial plexus block, saline versus ropivacaine, respectively. The rats from control group underwent general anesthesia only. The expression of proinflammatory cytokines in plasma and in hippocampus was measured. Open field test and new object recognition task were performed before surgery and on postoperative days (POD) 1, 3, and 7. Compared with control group, the level of cytokines in plasma and hippocampus revealed an obvious increase in surgery groups. The effect of brachial plexus block on decreasing cytokines was observed. The rats exposed to surgery without brachial plexus block showed behavior impairment. Our results indicated that nerve blockage could downregulate proinflammatory cytokines in hippocampus after humeral fixation surgery, which may ameliorate the postoperative cognitive dysfunction in young rats.